ASSISTANCE IN CREATING A NUTRITION STATUS DASHBOARD FOR DINAS KESEHATAN PROVINSI KALIMANTAN SELATAN - Lasari, Hadrianti H.D.; Sahamuddin, Sahamuddin; Nurikhwan, Pandji Winata; Juwita Hasri, Amalia; Firani, Dewi (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Indonesia continues to face nutritional problems that impact the lost generation. The prevalence of stunting, based on data from the Provincial Health Office of South Kalimantan, has decreased from 34.13% (2021) to 31.12% (2022). Similarly, the prevalence of underweight has also decreased from 24.3% (2021) to 22.1% (2022). If nutrition status data is not presented in real-time, it will result in slow handling of nutrition cases. Therefore, the community service team offered assistance in creating a nutrition status dashboard using Google Studio. The target audience for this activity was the staff and nutrition program managers at the Provincial Health Office of South Kalimantan. The community service method used was training and evaluation through pre and post-tests related to the assistance in creating the nutrition status dashboard. The results of both pre-test and post-test scores of the respondents did not follow a normal distribution due to the p-value being less than 0.05. Consequently, the Wilcoxon test was used, which showed a significant difference between the respondents' knowledge before and after receiving the material on creating a nutrition status dashboard at the Provincial Health Office of South Kalimantan.